The state of the wolf population in the Northern Azov region in the 1980s–2020s - Vitaly Voitovych (Theriologia Ukrainica)
Data on the first encounters with wolves in the early 1980s in the Northern Azov region are presented. The routes of their dispersal are considered, and a description of their active colonisation of the region during the abnormally warm winter of 1987–1988 is provided. The first wolf was caught in the autumn of 1987 in the vicinity of the Kamyani Mohyly Reserve, and encounters with these predators have been reported from five districts of the Northern Azov region. The first wolf packs included feral dogs and wolf-dog hybrids, which later disappeared. At first, the wolves were content with preyin on wild ungulates, hares and rodents, but from 1990 they began to actively visit large cattle burial grounds, which were overflowing with carcasses of domestic animals. Every year, starting in August, wolf packs began to cause damage to the inhabitants of the surrounding villages, killing large and small ruminants, dogs, and poultry. The number of these predators grew rapidly: there were cases of rabid wolves attacking people. Traditional hunting methods had no significant impact on their population. In the 2020s, some hunters acquired quad bikes and snowmobiles, the use of which, despite being prohibited, significantly increased the effectiveness of hunting. In some years, hunters killed 20–40 wolves during the winter season in an area of ~2000 square kilometres. However, winters with little or no snow and the start of active military operations sharply reduced hunting pressure, resulting in an increase in the number of wolves and more attacks on sheep farms and private households. The article provides a description of the areas used by wolves as dens, the nature of the dens themselves, their distance from settlements and water sources, the timing of births and the size of litters depending on the month of birth. Information is provided on the structure of wolf packs, the behaviour of wolves when hunting wild and domestic animals, and their use of the Reserve as a shelter. The need for continuous monitoring for the rational management of the wolf population and the maintenance of its safe sanitary and epidemiological status is justified.